Bread of angels - Smith, Patti (Random House, 2025)
"God whispers through a crease in the wallpaper, writes Patti Smith in this indelible account of her life as an artist. A post-World War II childhood unfolds in a condemned housing complex described in Dickensian detail: consumptive children, vanishing neighbors, an infested rat house, and a beguiling book of Irish fairy tales. We enter the child's world of the imagination where Smith, the captain of her loyal and beloved sibling army, vanquishes bullies, communes with the king of tortoises, and searches for sacred silver pennies. The most intimate of Smith's memoirs, Bread of Angels takes us through her teenage years when the first glimmers of art and romance take hold. Arthur Rimbaud and Bob Dylan emerge as creative heroes and role models as Smith starts to write poetry, then lyrics, merging both into the iconic recordings and songs such as Horses and Easter, "Dancing Barefoot" and "Because the Night." She leaves it all behind to marry her one true love, Fred "Sonic" Smith, with whom she creates a life of devotion and adventure on a canal in St. Clair Shores, Michigan, with ancient willows and fulsome pear trees. She builds a room of her own, furnished with a pillow of Moroccan silk, a Persian cup, inkwell and fountain pen. The couple spend nights in their landlocked Chris-Craft studying nautical maps and charting new adventures as they start their family. As Smith suffers profound losses, grief and gratitude are braided through years of caring for her children, rebuilding her life, and, finally, writing again-the one constant on a path driven by artistic freedom and the power of the imagination to transform the mundane into the beautiful, the commonplace into the magical, and pain into hope. In the final pages, we meet Patti Smith on the road again, the vagabond who travels to commune with herself, who lives to write and writes to live"--